Implementation of Twofold HB Beta SAE Model to Estimate Out-of-School Children with Disabilities in Indonesia - Maharani, Aisha; Ubaidillah, Azka; Adhi Kurniawan (Politeknik Statistika STIS, 2025)
Introduction/Main Objectives: The high percentage of out-of-school children with disabilities in Indonesia reveals a significant gap in educational participation. Background Problems: Due to the absence of disability-focused surveys, accurate data are only available at the national level, which is insufficient to represent regional conditions. Novelty: With the increasing demand for small area data, this study estimates the percentage of out-of-school children with disabilities at the provincial and district levels simultaneously, using small area estimation (SAE). Research Methods: This study applies SAE using a twofold subarea-level model with a Hierarchical Bayes (HB) beta approach, covering all 34 provinces and 514 districts/cities in Indonesia. This model was developed using data from the National Socio-Economic Survey (Susenas) and the Village Potential Statistics (Podes). Finding/Results: The twofold HB beta SAE model achieves higher precision than direct estimation, as shown by lower relative standard errors (RSE) across regions. Furthermore, spatial patterns indicate that the percentage of out-of-school children with disabilities is mostly between 35.36% and 45.34%, with clusters concentrated in Kalimantan and Papua.